2021
DOI: 10.7759/cureus.17063
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Steroid-Responsive Encephalopathy

Abstract: Hashimoto's encephalopathy (HE), also known as steroid-responsive encephalopathy, is associated with autoimmune-mediated thyroiditis. Onset is typically gradual often with evolution over the course of months. Characteristic symptoms include impaired concentration and memory, delusions, hallucinations, personality changes, incoordination, tremor, hemiparesis, seizures, and speech difficulties. Diagnosis is predicated upon discovery of elevated anti-thyroid antibodies, specifically anti-thyroid peroxidase (TPO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Depending on the case, corticosteroid therapy duration can vary from months to years ( 79 ). There is typically an improvement or complete resolution of the symptoms within a few months ( 5 ). In the event of disease recurrence or occurrence of side effects associated with steroids, other immunotherapies can be added, such as mycophenolate, azathioprine, cyclophosphamide, methotrexate, rituximab ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the case, corticosteroid therapy duration can vary from months to years ( 79 ). There is typically an improvement or complete resolution of the symptoms within a few months ( 5 ). In the event of disease recurrence or occurrence of side effects associated with steroids, other immunotherapies can be added, such as mycophenolate, azathioprine, cyclophosphamide, methotrexate, rituximab ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, IVIG was used as the first-line therapy, either alone or in combination with steroid therapy ( 5 , 6 , 9 , 10 ). These cases were published in the last 7 years, so the initial use of IVIG may be the result of the data found in literature which sustains the beneficial effects of IVIG in the treatment of HE.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that ATA are the hallmark of HE rather than playing a direct role in the pathogenesis of HE [7]. Hence, the more accurate name for this condition is steroid-responsive encephalopathy associated with autoimmune thyroiditis (SREAT) [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…There is a broad spectrum of presenting manifestations; however, encephalopathy manifesting with abrupt confusion with an altered level of consciousness is the hallmark presentation [8,10]. Two patterns of cognitive dysfunction are predominant; a stroke-like pattern which is more acute to subacute, and a gradual diffuse progressive pattern which might result in dementia, hallucination, or even lethargy, progressing to coma in extreme cases [8,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation